SISTEM PENGUKURAN DAN PEMROSESAN DATA MEDAN LISTRIK TELLURIK - Asmoro Hadi, Nasio
Telluric electrical field data measurement and processing system was built. The measurement system consist pair of porespote electrode, low noise instrumentation amplifier (IC AD 524), Butterworth low pass filter and non inverting amplifier in the unity, and Analog to Digital Converter (PCL 812PG ADC). Laboratory test of them have range of frequency measure similarity under 2.5 Hz. Field strength ratio (E€ /Eb) test and coherency test have average similarity 97 %. The processing system used DFT cascade, decimation, digital filter non aliasing and Robust estimation analysis. The result of Robust estimation to be compared with List Square (LS) estimation. Robust more stable than LS, that means Robust more resistance to change of data or noise.